Mechanisms of Beta-Blockers Action in Patients with Heart Failure - Prijic, Sergej; Buchhorn, Reiner (Reviews on Recent Clinical Trials, 2014)
Patients with chronic heart failure have prolonged sympathetic stimulation and subsequent worsening of the failing heart function. Beta-blockers (non-selective, cardio-selective, and non-selective with ancillary properties) counteract the effects of prolonged sympathetic stimulation. Beta-blocker therapy results in the improvement of the left ventricular systolic and diastolic function, reversal remodeling, heart rate control, effective prevention of the malignant arrhythmias, and lowering of the both cardiac afterload and preload in patients with chronic heart failure.
Keywords: heart failure